Kidney‐Targeted Nanoparticles Loaded with the Natural Antioxidant Rosmarinic Acid for Acute Kidney Injury Treatment. Issue 48 (17th October 2022) - Li, Jiajia; Duan, Qijia; Wei, Xiaona; Wu, Jianping; Yang, Qiongqiong
Abstract: Acute kidney injury (AKI) is a common clinical disease with high morbidity and mortality, and with a lack of effective drugs for treatment. Oxidative stress is very important in the occurrence and progression of AKI, and antioxidants use is one of the promising treatments. Rosmarinic acid (RA) is a ubiquitous natural polyphenol with powerful antioxidant and anti‐inflammatory activities. Due to its inherent characteristic with poor water solubility and inferior bioavailability, its clinical application is impeded. Hence, the authors design a nanoparticle for effectively delivering RA, which is a chemical complex of RA and fourth‐generation poly‐amidoamine‐based amphiphilic polymer (G4‐PAMAM). The nanoparticle is modified with l‐serine due to the specific interaction between kidney injury molecule–1 (Kim‐1) and serine, which eventually generates a promising AKI kidney–targeting nanoparticle (S‐G‐R). The S‐G‐R is rapidly cumulated and long‐term retained in ischemia‐reperfusion–induced AKI kidneys, especially in the damaged renal tubular cells. The S‐G‐R exhibits more excellent antioxidative and antiapoptotic effects in vitro and has a more outstanding ability to improve the renal function, repair damaged renal tissue, and decrease oxidative stress, inflammatory response and apoptosis of tubular cells in vivo. Overall, this study might develop a safe and effective targeting strategy for the therapy of AKI. Abstract : This study designs a promising acute kidney injury (AKI) kidney‐targeting nanoparticle (Ser‐PEG2K ‐G4‐PAMAM‐RA‐COOH, S‐G‐R), which is a chemical complex of rosmarinic acid (RA), fourth‐generation poly‐amidoamine‐based amphiphilic polymer (G4‐PAMAM), and l‐serine. The S‐G‐R exhibits more excellent antioxidative and antiapoptotic effects compared with free RA and non‐targeted group (m‐PEG2K ‐G4‐PAMAM‐RA‐COOH, G‐R) in vitro and in vivo.